Attainment of lead titanate - Through the thermal decomposition of coprecipitated 8-hydroxyquinolinate precursors - Zorel, H. E.; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP] (Kluwer Academic Publ, 2004)
Crystalline PbTiO3 was obtained through the thermal decomposition of 8-hydroxyquinolinate of lead(II) and that of titanium(IV), which was monitored by TG/DTG/DTA under different atmospheric conditions and with varying heating rates. The compound was prepared from adding 8-hydroxyquinoline solution in the solution of metallic ions Pb(II):Ti(IV) (1:1) Linder constant stirring at 3degreesC, having the pH adjusted to 10. The results of these investigations show that different thermal behavior related to the precursor occurred and also the consequent formation of residues which have different crystallinities. No carbonate residues from the thermal decomposition could be determined by XRD and IR. Only PbTiO3 was observed and confirmed by DSC at 470degreesC, temperature lower than the tetragonal-cubic transition.
Keywords: 8-hydroxyquinoline; PbTiO3; precursor powder